A new species of Odontella from Tierra del Fuego and notes on Afrodontella Deharveng, 1981 (Collembola: Odontellidae) - Arbea, Javier I.; Palacios-Vargas, José G. (Zootaxa, 2020)
Odontella rapoporti sp. nov., from Tierra del Fuego is described, as the third species of the Odontella lobata group, which has a subantarctic distribution. The new species is similar to O. lobata and O. setosa, but can be distinguished from them by the number of chaetae on the dens (6 or 7 chaetae in O. setosa vs. 5 chaetae in the other species) and the number of chaetae in the distal whorl of the tibiotarsus (9 chaetae in O. lobata vs. 11 in the other species). The closely related monotypic genus Afrodontella Deharveng, 1981, and its type species (A. septemlobata) are described.